Entrepreneurial education for engineers - BUGAIAN, Larisa (Journal of Social Sciences, 2018)
In a knowledge-based society, higher education institutions become agents that generate the welfare of society and its members. They become identities that create knowledge based on scientific research that, being implemented in society, turn into practical results. This knowledge forms the competences to be formed through university study programs. A modern approach to developing a study program that meets the current needs of the society should be geared to the training of competences that a professional has to possess, that will be assimilated by the dynamic social-economic environment. General requirement: the engineering profession should be taught by combining engineering and managerial competences.